Ultrasonographic Demonstration of the Tissue Microvasculature in Children: Microvascular Ultrasonography Versus Conventional Color Doppler Ultrasonography - Yoo, Joonghyun (Korean J Radiol, 2020)
Microvascular ultrasonographic imaging is the most recent and unique Doppler ultrasound technique. It uses an advanced clutter filter that can remove clutter artifacts and preserve the low-velocity microvascular flow signal. The potential advantages of microvascular ultrasonography are its superiority in detection and visualization of the small blood vessels in tissues, providing radiologists with more information on the vascular structures. Therefore, it has shown particular value in the clinical fields. The aim of this study was to provide microvascular ultrasonographic images for the tissue microvasculature, including the brain, thyroid gland, kidney, urinary bladder, small bowel, ovary, testis, lymph node, and hemangiomas in children, focusing on the comparison with conventional color Doppler ultrasonographic images.